Impact of CAD/CAM systems on the precision of fixed dental prostheses: a systematic literature review - Gomez, Esteban (Revista JRG de Estudos Acadêmicos, 2026)
The objective of this study was to evaluate, through a systematic review of the literature, the impact of computer-aided design and computer-aided manufacturing (CAD/CAM) systems on the accuracy of fixed dental prostheses, considering outcomes related to marginal and internal fit. The review was conducted in accordance with the PRISMA 2020 guidelines, with searches performed in the PubMed/MEDLINE and SciELO databases, complemented by manual reference tracking, covering publications from the last ten years. Laboratory and clinical studies that quantitatively assessed the marginal or internal fit of single crowns and fixed partial dentures fabricated using CAD/CAM systems, either in comparison with conventional methods or among different digital workflows, were included. The results demonstrated that, in general, CAD/CAM-fabricated fixed prostheses exhibit fit values considered clinically acceptable, often equivalent to or superior to those obtained with conventional methods, particularly for single-unit restorations. However, significant variability among studies was observed, mainly attributable to differences in the CAD/CAM systems employed, the restorative materials evaluated, digital design parameters, and fit measurement methods. Materials such as zirconia and lithium disilicate showed satisfactory performance, although influenced by specific stages of digital processing. It is concluded that CAD/CAM systems represent a reliable technology for the fabrication of fixed dental prostheses with adequate dimensional accuracy, provided they are applied within well-defined clinical-laboratory protocols. Furthermore, greater methodological standardization in future studies is necessary to strengthen the level of available scientific evidence.